2013
DOI: 10.1111/arcm.12058
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Neutron Analysis Techniques for Detecting The Concentration And Distribution of Chloride Ions in Archaeological Iron

Abstract: Chloride (Cl) ions diffuse into iron objects during burial and drive corrosion after excavation. Located under corrosion layers, Cl is inaccessible to many analytical techniques. Neutron analysis offers non-destructive avenues for determining Cl content and distribution in objects. A pilot study used prompt gamma activation analysis (PGAA) and prompt gamma activation imaging (PGAI) to analyse the bulk concentration and longitudinal distribution of Cl in archaeological iron objects. This correlated with the obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Assuming that the calculations can be made and the values obtained are reliable, what do they mean for heritage artefacts? Study has shown that the corrosion of chloride-infested archaeological iron, for example, is not a process that occurs evenly across the metal surface [40]. Instead, it is localised in pits and this localised corrosion can cause catastrophic damage and break-up of an artefact long before the metal core has been converted by corrosion processes.…”
Section: Considerationsmentioning
confidence: 99%
“…Assuming that the calculations can be made and the values obtained are reliable, what do they mean for heritage artefacts? Study has shown that the corrosion of chloride-infested archaeological iron, for example, is not a process that occurs evenly across the metal surface [40]. Instead, it is localised in pits and this localised corrosion can cause catastrophic damage and break-up of an artefact long before the metal core has been converted by corrosion processes.…”
Section: Considerationsmentioning
confidence: 99%
“…cross-sectional slices. Individual cross-sections may consist of X-radiographs, [20] diffraction patterns, [21] neutron radiographs [22] or spectroscopic data [21] depending on the material and system being studied. The most common tomography, X-ray computed tomography (CT), has been shown to be a highly effective non-destructive method for studying archaeology, [23][24][25] corrosion [19,26,27] and metallography [28,29], particularly when used in combination with 2D analytical methods.…”
Section: Tomographic Analyses Create a 3d Representation Of A Sample mentioning
confidence: 99%
“…A similar methodology was used in another study, where it was possible to establish a correlation between the longitudinal chlorine profile and the degree of corrosion in archaeological iron nails (Watkinson et al, 2014). After excavation, oxidation forms ferrous chloride and hydroxide, which cause cracking, fragmentation and break-up of the objects.…”
Section: 1analysis Of Archaeological Ironmentioning
confidence: 99%